Disaster in Sufi Interpretation: Dialecticalising the Sufistic Trilogy of Abdul Qadir al-Jilani, Ibn ’Arabi and Achmad Asrori al-Ishaqi - Ainul; Chafid; Hadi (Journal of Islamic Civilization, 2023)
The phenomenon of disaster is an inseparable part of human life. The understanding of it is often considered as a will of God or a natural occurrence, which consequently gives a non-anticipatory and desperate perspective. This study aims to reveal the articulation of disaster according to the idea of the Qur'an based on Sufi interpretation by dialecticism, the interpretations of Abdul Qadir al-Jilani, Ibn 'Arabi, and Achmad Asrori al-Ishaqi, from now on referred to as the "Sufi interpretation trilogy." This research is a literature study using the perspective of Sufi interpretation. Through the reading of this Sufi interpretation trilogy, the author reveals that the meaning of disaster, according to the three Sufis above, can be connected in singularity. Al-Jilani's reading with two types of understanding of disaster between destiny and the impact of damage marks that humans understand with their efforts in facing a disaster. Then, Ibn 'Arabi's reading, with its understanding of the phenomenal Absolute, makes us aware of not assuming disaster as punishment by always relying on God's power (religious-humanism). Meanwhile, al-Ishaqi on all these matters is simplified to the level of praxis, that natural disasters or calamities are images of human and natural relations that are not friendly to each other. The research thus implies a different perspective on natural disasters, which can be caused by religious (injustice) or ecological (exploitation) human mischief.